(untitled) (Journal of Chemical Engineering, 2014)
Pectin is widely used as a gelling agent, thickener, emulsifier and stabilizer in different food processing operations. Chemically it represents a polysaccharide, which is present in different amount in cell walls of all land plants. But citrus fruit is very rich in this component and can be used as source for its production commercially. In this study, lemon peel was selected as a representative of the citrus fruit family to extract pectin because of the abundance of the fruit in Bangladesh. Grounded lemon peel was digested in a solution of 0.01N HCl at a temperature of 80-90°C for 1.5 hours. The solid mass is filtered out and the filtrate is treated with different low molecular weight alcohol such as methanol, ethanol and isopropanol to precipitate the pectin out. The precipitate is dried at 40°C under vacuum. The structure of the product is yet to confirm by Fourier transform infrared spectroscopy (FTIR) analysis. The product is characterized by the parameters as methoxyl content, anhydrouronic acid content, degree of esterification, equivalent weight and intrinsic viscosity. The characteristic parameters are found to be in the same range as those shown by the product proposed in the market as Pectin. The yield of pectin extracted by the present method is as low as 1.08 1.38%, which is too low to make the method feasible for commercial purposes. Researchers are underway to improve the yield as well quality of the product. DOI: http://dx.doi.org/10.3329/jce.v27i2.17797 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 2, December 2012: 25-30